2011
DOI: 10.4049/jimmunol.1004030
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Variation of the Response of T Cells to Antigen

Abstract: Circadian clocks regulate many important aspects of physiology, and their disturbance leads to various medical conditions. Circadian variations have been found in immune system variables, including daily rhythms in circulating WBC numbers and serum concentration of cytokines. However, control of immune functional responses by the circadian clock has remained relatively unexplored. In this study, we show that mouse lymph nodes exhibit rhythmic clock gene expression. T cells from lymph nodes collected over 24 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
171
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(182 citation statements)
references
References 72 publications
(79 reference statements)
4
171
0
Order By: Relevance
“…Consistent with the possible importance of this regulation, clock protein misexpression and/or a lack of circadian control has been documented in multiple tumor types (Hwang-Verslues et al, 2013; Luo et al, 2012;Zhao et al, 2013) and immortalized cell lines (Yeom et al, 2010). In normal physiology, circadian cell division has been documented in adult hippocampal neurogenesis (BouchardCannon et al, 2013), in intestinal and skin epithelial cell division (Geyfman et al, 2012;Janich et al, 2013;Karpowicz et al, 2013), and in multiple immune cell populations (Fortier et al, 2011;Keller et al, 2009) -essentially anywhere that cell division occurs in adult animals.…”
Section: From Cell Cycle To Tissues: Circadian Control Of Tissue Homementioning
confidence: 78%
See 1 more Smart Citation
“…Consistent with the possible importance of this regulation, clock protein misexpression and/or a lack of circadian control has been documented in multiple tumor types (Hwang-Verslues et al, 2013; Luo et al, 2012;Zhao et al, 2013) and immortalized cell lines (Yeom et al, 2010). In normal physiology, circadian cell division has been documented in adult hippocampal neurogenesis (BouchardCannon et al, 2013), in intestinal and skin epithelial cell division (Geyfman et al, 2012;Janich et al, 2013;Karpowicz et al, 2013), and in multiple immune cell populations (Fortier et al, 2011;Keller et al, 2009) -essentially anywhere that cell division occurs in adult animals.…”
Section: From Cell Cycle To Tissues: Circadian Control Of Tissue Homementioning
confidence: 78%
“…Bmal1 deficiency is also linked to reduced osteoblast proliferation in adult mice, although a circadian role here has not been proven . Furthermore, in the complex differentiation processes leading to the development of the immune system, T h 17 T helper cell development is regulated by the circadian factors REV-ERBα and RORγ (RORC -Mouse Genome Informatics) , and circadian cytokine release in vivo and in vitro is likely to influence other immune cell subpopulations (Fortier et al, 2011;Keller et al, 2009;Wang et al, 2011). Finally, in addition to regulating metabolism, multiple circadian clock genes directly regulate the size and differentiation of pancreatic islets (Marcheva et al, 2010).…”
Section: From Tissue Homeostasis To Stem Cells: Circadian Control Of mentioning
confidence: 99%
“…Among them, the innate and adaptive immune systems were shown to display daily rhythms in rodents and humans (14). This includes rhythms in cell counts in the blood (15)(16)(17)(18) and peripheral lymphoid organs (19), lymphocyte proliferation (20), cytokine levels in the blood (21)(22)(23)(24), and following ex vivo stimulation with various stimuli (16,19,(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…In central and peripheral clocks, rhythms with a period of ∼ 24 h are generated by autoregulatory feedback loops involving clock genes (e.g., CLOCK, BMAL1, Period or PER1-3, Cryptochrome or CRY1-2) (32). Hence, immune cells (e.g., monocytes/macrophages, lymphocytes) have the molecular clock machinery and display circadian gene expression (19,20,25,(33)(34)(35).…”
mentioning
confidence: 99%
“…Furthermore mice display time-of-day dependent responses to bacterial endotoxins and exotoxins, and pro-inflammatory cytokines (83,84). Clock disruption studies have shown that T-cell antigen response is partially mediated by clock (84).…”
Section: Immunementioning
confidence: 99%